MUDWHELKS (GASTROPODA: POTAMIDIDAE) FROM MANGROVES OF UJUNG KULON NATIONAL PARK, BANTEN - MUJIONO, NOVA (Jurnal Biologi Udayana; Vol 13 No 2 (2009): JURNAL BIOLOGI, 2009)
A study of Potamididae snail from the mangrove ecosystem in Ujung Kulon National Park was conducted, regarding to its diversity, shell characters and habitat characters. This study was carried out in 2008 during drought and rainy season. At the eight stations observed, seven species and four genera of Potamididae snail were identified. Compared with previous study, this study added new information from obtaining one genus (Cerithidea) of three species (Cerithidea weyersi, C. quadrata and Cerithideopsilla alata)
Keywords: Potamididae; shell’s characters; mangrove; Ujung Kulon